2000
DOI: 10.2307/2648099
|View full text |Cite
|
Sign up to set email alerts
|

Son preference and sex composition of children: Evidence from india

Abstract: Although the effect of son preference on sex composition of children ever born is undetectable in national-level estimates that aggregate across all families, this article provides empirical evidence from India that son preference has two pronounced and predictable family-level effects on the sex composition of children ever born. First, data from India show that smaller families have a significantly higher proportion of sons than larger families. Second, socially and economically disadvantaged couples and cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
315
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(345 citation statements)
references
References 31 publications
14
315
3
Order By: Relevance
“…Previous studies have shown that a child's birth order and the number, sex and ordering of her siblings matters for her survival and well-being (Clark 2000;Pande 2003). Our results suggest that the number of siblings has important implications for childrens' growth (Model 9 in Table 5), but does not explain the excess male advantage in China.…”
Section: Discussioncontrasting
confidence: 36%
See 1 more Smart Citation
“…Previous studies have shown that a child's birth order and the number, sex and ordering of her siblings matters for her survival and well-being (Clark 2000;Pande 2003). Our results suggest that the number of siblings has important implications for childrens' growth (Model 9 in Table 5), but does not explain the excess male advantage in China.…”
Section: Discussioncontrasting
confidence: 36%
“…For example, Clark (2000) reports that in India, rural women desire a greater proportion of sons than do urban women, and Ren (1995) notes relatively higher child mortality among female children in rural areas in China.…”
Section: Discussionmentioning
confidence: 99%
“…We use, as an instrument, a binary variable that is equal to one if the first-born child is a girl, and to zero otherwise. The effects of the first-born's gender have been analysed in various papers (Rosenzweig and Wolpin, 2000), in Asia (Chowdhury and Bairagi, 1990;Clark, 2000;Dreze and Murthi, 2001;Lee, 2008;Li and Wu, 2011;Milazzo, 2014b), and more recently, in Sub-Saharan Africa (Milazzo, 2014a). In Nepal, as in other countries, there is a strong preference for boys.…”
Section: Empirical Strategymentioning
confidence: 99%
“…Due to this preference for sons, many couples in South and East Asia face a difficult choice: either to risk having no sons and lose face in front of their friends and family, or to take deliberate steps to ensure that at least one of their children is male. Many couples make the second choice by means of sex-selective abortions and infanticide, thus contributing to the abnormally high ratio of male to female children in their countries (14)(15)(16).…”
mentioning
confidence: 99%